ANALISIS KINERJA INLISLITE V.3.1 SEBAGAI SARANA TEMU KEMBALI PERPUSTAKAAN KEMENTERIAN PANRB - Nur Sanny Rahmawati; Nina Mayesti (UIN Imam Bonjol Padang, 2021)
This article discusses the performance analysis of INLISLite which is used in the Kementerian PANRB’s Library as a retrieval system. This article aims to identify the performance of the INLISLite used in the Kementerian PANRB’s Library. The approach used in this research is descriptive qualitative with participatory observation methods. Furthermore, the aspects analyzed in the object of this study are recall, precision, and response time from the INLISLite of the Kementerian PANRB’s Library. The results obtained by the recall value ranged from 0.928 to 1, while the precision value was in the range 0.76 to 1 which was obtained through a simple search. Additionally, the average response time obtained based on searching through collection titles is 0.206 seconds. Meanwhile, for tracing through the subject, the response time obtained was 0.214 seconds. Even though the system is quite effective, there are still shortcomings in terms of features such as the absence of live chat with librarians so that it does not provide alternative options for users to communicate.